Effects of physical activity on endothelial progenitor cells (EPCs) - DE BIASE, CHIARA; DE ROSA, ROBERTA; LUCIANO, ROSSELLA; DE LUCA, STEFANIA; CAPUANO, ERNESTO; TRIMARCO, BRUNO; GALASSO, GENNARO (Frontiers in Physiology, 2014)
Physical activity has a therapeutic role in cardiovascular disease (CVD), through its beneficial effects on endothelial function and cardiovascular system. Circulating endothelial progenitor cells (EPCs) are bone marrow (BM) derived cells that represent a novel therapeutic target in CVD patients, because of their ability to home to sites of ischemic injury and repair the damaged vessels. Several studies show that physical activity results in a significant increase in circulating EPCs, and, in particular, there are some evidence of the beneficial exercise-induced effects on EPCs activity in CVD settings, including coronary artery disease (CAD), heart failure (HF) and peripheral artery disease (PAD). The aim of this paper is to review the current evidence about the beneficial effects of physical exercise on endothelial function and EPCs levels and activity in both healthy subjects and patients with CVD.